2017
DOI: 10.1002/cptc.201700103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substituent‐Dependent Photoinduced Intramolecular Charge Transfer on the Photochromism of Hemithioindigos

Abstract: A series of N,N′‐diarylamine‐modified hemithioindigos (HTIs) were synthesized and characterized. Photochemical Z/E isomerization around the C=C double bond occurred for all novel HTIs in various solvents. Due to a strong donor–acceptor π‐conjugated structure, the novel HTIs exhibited a strong red shift and clear solvatochromism in steady‐state absorption and fluorescence spectroscopic measurements, respectively. An intramolecular charge transfer (ICT) from the diarylamine‐substituted stilbene component (donor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Determining PSS by spectrophotometry required HOTub solution concentrations well above their aqueous solubility limit (as do NMR measurements), so we constrained our measurements to water‐cosolvent mixtures. We do not assume that the average cellular PSS or relaxation rates for HTIs will be identical to those determined in cuvette measurements, as in cellulo HTIs will be in heterogenous environments depending on cellular biolocalisation (e.g., into lipid membranes or aqueous cytosol) and the absorption band intensities and positions, quantum yields of photoisomerisations, and the thermal E to Z relaxation rate are all known to be solvent dependent . However, we expected that the trends of PSS wavelength dependency as measured in UV/Vis would reasonably correspond to those in the cellular context.…”
Section: Resultsmentioning
confidence: 99%
“…Determining PSS by spectrophotometry required HOTub solution concentrations well above their aqueous solubility limit (as do NMR measurements), so we constrained our measurements to water‐cosolvent mixtures. We do not assume that the average cellular PSS or relaxation rates for HTIs will be identical to those determined in cuvette measurements, as in cellulo HTIs will be in heterogenous environments depending on cellular biolocalisation (e.g., into lipid membranes or aqueous cytosol) and the absorption band intensities and positions, quantum yields of photoisomerisations, and the thermal E to Z relaxation rate are all known to be solvent dependent . However, we expected that the trends of PSS wavelength dependency as measured in UV/Vis would reasonably correspond to those in the cellular context.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently established TICT formation in hemithioindigo (HTI) chromophores (Figure )an emerging class of photoswitches , and used this excited-state pathway for controlling the type of light-induced molecular motion by simply changing the solvent . A similar charge transfer behavior in the excited state was also suggested for N , N -diarylamine-substituted HTIs . With the additional TICT state, it is possible to either favor double-bond isomerization (DBI) in apolar solvents or single-bond twisting (SBT) in strongly polar solvents using the same molecule (Figure b).…”
Section: Introductionmentioning
confidence: 89%
“…21 A similar charge transfer behavior in the excited state was also suggested for N,N-diarylamine-substituted HTIs. 28 With the additional TICT state, it is possible to either favor double-bond isomerization (DBI) in apolar solvents or single-bond twisting (SBT) in strongly polar solvents using the same molecule (Figure 1b). The reason for this behavior is the inherently most polar character of the TICT state as compared to other excited states (Figure 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wang et al [ 22 ] reported the reaction of thiophenols 44b with chloroacetic acid 68 in the presence of sodium hydroxide to form the 2‐(arylthio)acetic acid 69 , which cyclized to the benzo[b]thiophen‐3‐ols 70 upon heating with thionyl chloride followed by heating the formed acid chloride in 1, 2‐dichloroethane in the presence of AlCl 3 . Condensation of compound 70 with 2‐nitrobezaldehyde 71 in ethanol formed the nitroarylidene 72 , which reduced in anhydrous acetic acid in the presence of tin chloride to achieve the aminoarylidine 73 , which undergoes intramolecular cyclization under irradiation with UV light to the benzothieno[3,2‐ b ]quinoline 74 (Scheme 13).…”
Section: Synthesis and Reactivitymentioning
confidence: 99%